2003
DOI: 10.1046/j.1523-1755.2003.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high protein diet on stone-forming propensity and bone loss in rats

Abstract: Both the kidney and bone contribute to the pathogenesis of hypercalciuria during high casein diet in rats. Hypocitraturia is probably renal in origin. This rat model will be useful in elucidating the mechanisms by which high protein intake increases the risk of nephrolithiasis and bone loss in human beings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 29 publications
6
72
0
2
Order By: Relevance
“…These increases were likely due to greater contents of sulfur amino acids and organic phosphorus, respectively, in the HP diets (20). Hypocitraturia, also associated with high-protein intakes (12), was observed in the HP groups, as well, as a consequence of a decrease in proximal tubule reabsorption of citrate and an impairment of citrate transport in the kidney (20).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These increases were likely due to greater contents of sulfur amino acids and organic phosphorus, respectively, in the HP diets (20). Hypocitraturia, also associated with high-protein intakes (12), was observed in the HP groups, as well, as a consequence of a decrease in proximal tubule reabsorption of citrate and an impairment of citrate transport in the kidney (20).…”
Section: Discussionmentioning
confidence: 90%
“…However, other reports suggest that such a diet may alter calcium homeostasis in ways that could lead to bone loss (11,12). The metabolic acidosis, derived from sulfur amino acids catabolism, would also exert a direct stimulatory effect on bone resorption and an inhibitory action on matrix mineralization (13,14).…”
mentioning
confidence: 99%
“…However, we cannot completely rule out a role in this regard for a separate urinary factor(s), cosegregating with, but independent from, urinary urea concentration. For example, although high protein diets increase urinary urea excretion, they also decrease urinary pH while increasing urinary ammonium, net acid, phosphorous, and calcium excretion (2). Because Hlad and coworkers (15) showed that low urinary pH increases transport of urinary sodium and chloride (they did not study urea) across dog bladder in vivo and because recent work in sheep rumen epithelium has demonstrated a lumenal pH modification of urea transport, likely by affecting UT-B (1), we cannot rule out an effect of urine pH on urothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Animal protein intake represents an acid load and increases urinary calcium, (35)(36)(37) whereas alkali administration decreases it (9,10). Thus, the positive association between urinary sulfate, a marker for animal protein intake, and urinary calcium was expected.…”
Section: Discussionmentioning
confidence: 99%